Design of Fishing Smoke (saltization) Equipment and Its Process for Improving the Economy Community in Lampulo Banda Aceh - Edy Fradinata; Zurnila Marli Kesuma (Jurnal Pengabdian Pada Masyarakat, 2020)
Wooden fish (Keumamah) is made from tuna fish. It is one of the characteristic main commodities from Aceh Province where it is bordered by two major oceans of the world, the Indian Ocean and the Malacca Strait. This geographical condition is very favorable because the ocean stores abundant marine products, especially tuna fish and tongkol fish. The keumamah is one of the traditional favorable food product in Aceh. In Aceh, that excess fish from the rest of the fishermen's catch will usually be preserved by means of saltization, fumigation and boiling. However, wooden fish have not been able to provide a wider economic improvement impact on the surrounding community, especially the lampulo coastal area which incidentally as a fisherman. So there needs to be an increase in the economy for home-scale entrepreneurs in Aceh province. Development of fish processing equipment shaped like cupboards, sturdy, sleek, and ergonomic combined with packaging design, sales techniques and marketing management and entrepreneurship for small business groups in lampulo-Banda Aceh. The development of fish processing equipment shaped like cupboards, sturdy, sleek, and ergonomic combined with sales and marketing management techniques and entrepreneurship for these small business groups will develop tuna fish products that can be processed with various types of culinary food such as: fish nuggets, crackers fish, fish balls, and kemamah. The problem can be solved when fish processing methods emerge to become a variety of culinary, with higher production capacity to the community about good and right fish processing. This fish processing innovation in the form of processing fish into a variety of culinary that combines several processing functions such as smoking, grinding, drying, etc.